2014
DOI: 10.1158/0008-5472.can-13-3572
|View full text |Cite
|
Sign up to set email alerts
|

H3K9 Histone Methyltransferase, KMT1E/SETDB1, Cooperates with the SMAD2/3 Pathway to Suppress Lung Cancer Metastasis

Abstract: Aberrant histone methylation is a frequent event during tumor development and progression. KMT1E (also known as SETDB1) is a histone H3K9 methyltransferase that contributes to epigenetic silencing of both oncogenes and tumor suppressor genes in cancer cells. In this report, we demonstrate that KMT1E acts as a metastasis suppressor that is strongly downregulated in highly metastatic lung cancer cells. Restoring KMT1E expression in this setting suppressed filopodia formation, migration, and invasive behavior. Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 44 publications
4
60
0
Order By: Relevance
“…In a melanoma zebrafish model, overexpression of SETDB1 increased local invasiveness of the tumor . However, in another study, inactivation of SETDB1 promoted metastasis of lung cancer cells in zebrafish and mouse models . Interestingly, both prometastatic and antimetastatic functions of SETDB1 have been observed in lung cancer with different cell line models used .…”
Section: Discussionmentioning
confidence: 98%
“…In a melanoma zebrafish model, overexpression of SETDB1 increased local invasiveness of the tumor . However, in another study, inactivation of SETDB1 promoted metastasis of lung cancer cells in zebrafish and mouse models . Interestingly, both prometastatic and antimetastatic functions of SETDB1 have been observed in lung cancer with different cell line models used .…”
Section: Discussionmentioning
confidence: 98%
“…As described in the present study, JARID1D is lost and downregulated in a substantial portion of metastatic prostate tumors. The H3K9 methyltransferase SETDB1, which appears to inhibit metastasis of lung cancer cells, is strongly downregulated in lung cancer cells (53). …”
Section: Discussionmentioning
confidence: 99%
“…It represses a large set of genes including HOX genes for melanoma progression [127] and confers outgrowth and advantages of liver cancer cells through methylating and stabilizing the oncogenic p53 mutants [128]. Surprisingly, it has also been shown that SETDB1 cooperates with SMAD2/3 to suppress EMT and metastasis of lung cancer cells [130]. …”
Section: Permissive Histone Modifications In Emtmentioning
confidence: 99%